2016
DOI: 10.1177/0890334416658246
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Support in Spanish Neonatal Intensive Care Units and the Baby-Friendly Hospital Initiative

Abstract: The Spanish NICUs in hospitals with BFHI accreditation or in the process of being accredited have better implementation of practices to promote and support breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The groups identified in the correspondence analysis showed a pattern similar to other studies in which friendly paediatric breastfeeding practices may demonstrate a positive effect on breastfeeding at hospital discharge [ 19 , 37 ], an important condition for maintaining this practice [ 38 ].…”
Section: Discussionsupporting
confidence: 76%
“…The groups identified in the correspondence analysis showed a pattern similar to other studies in which friendly paediatric breastfeeding practices may demonstrate a positive effect on breastfeeding at hospital discharge [ 19 , 37 ], an important condition for maintaining this practice [ 38 ].…”
Section: Discussionsupporting
confidence: 76%
“…It has been shown that compliance with BFHI standards was significantly higher when reported by staff/managers than parents themselves (Haiek, ). Still, health care professional self‐reports remain one of the most accessible sources of information to measure compliance, and comparison of the present results was done with such studies (Alonso‐Diaz et al, ; Grizzard et al, ; Maastrup et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…Higher scores obtained by neonatal wards in hospitals ever‐designated Baby‐friendly may be related to the fact that BFHI certification includes some practices related to neonatal care, but it may also demonstrate that maternity and neonatal wards do not operate in isolation (Taylor, Gribble, Sheehan, Schmied, & Dykes, ) and the certification process in one ward may have a beneficial effect on the revision of policies and practices of the other one (Alonso‐Diaz et al, ). Even though only four countries in the present survey had a Baby‐friendly neonatal certification process separate from the original one, 60% of the respondents expressed intentions to obtain or maintain BFHI certification for their neonatal ward.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations